Evidence of Lineage 1 and 3 West Nile Virus in Person with Neuroinvasive Disease, Nebraska, USA, 2023 - Davis, Emily; Velez, Jason; Hamik, Jeff; Fitzpatrick, Kelly; Haley, Jacki; Eschliman, Jeremy; Panella, Amanda; Staples, J. Erin; Lambert, Amy; Donahue, Matthew; Brault, Aaron C.; Hughes, Holly R. (Emerging infectious diseases, 2024)
West Nile virus (WNV) is the most common cause of human arboviral disease in the contiguous United States, where only lineage 1 (L1) WNV had been found. In 2023, an immunocompetent patient was hospitalized in Nebraska with West Nile neuroinvasive disease and multisystem organ failure. Testing at the Centers for Disease Control and Prevention indicated an unusually high viral load and acute antibody response. Upon sequencing of serum and cerebrospinal fluid, we detected lineage 3 (L3) and L1 WNV genomes. L3 WNV had previously only been found in Central Europe in mosquitoes. The identification of L3 WNV in the United States and the observed clinical and laboratory features raise questions about the potential effect of L3 WNV on the transmission dynamics and pathogenicity of WNV infections. Determining the distribution and prevalence of L3 WNV in the United States and any public health and clinical implications is critical.